2001
DOI: 10.1002/1099-1166(200102)16:2<223::aid-gps323>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and effectiveness of atypical antipsychotics in male geriatric inpatients

Abstract: The atypical antipsychotics are gradually becoming the mainstay of treatment for psychosis in the elderly. The present study examines the effectiveness and tolerability of risperidone and olanzapine treatment in 34 matched male patients admitted to a VA Medical Center geriatric inpatient unit. The Positive and Negative Syndrome Scale for Schizophrenia (PANSS), the Cohen‐Mansfield Agitation Inventory (CMAI), the Rating Scale for Side‐Effects, the Extra‐Pyramidal Rating Scale, and the Mini‐Mental State Examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The literature on risperidone for the treatment of schizophrenia and related disorders in elderly patients includes a case series, seven retrospective studies (four retrospective comparison studies) ( Table 4), six open-label studies, and one double-blind comparison trial [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] (see Table 4). All published reports found a good-to-moderate response with risperidone.…”
Section: Risperidonementioning
confidence: 99%
See 2 more Smart Citations
“…The literature on risperidone for the treatment of schizophrenia and related disorders in elderly patients includes a case series, seven retrospective studies (four retrospective comparison studies) ( Table 4), six open-label studies, and one double-blind comparison trial [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] (see Table 4). All published reports found a good-to-moderate response with risperidone.…”
Section: Risperidonementioning
confidence: 99%
“…In a retrospective comparison study of 34 elderly hospitalized patients receiving either risperidone (n=17) or olanzapine (n=17), Verma et al [50] found no differences between the two groups with regard to length of hospitalization or efficacy. The investigators noted that the daily cost of risperidone was one-third that of olanzapine.…”
Section: Risperidonementioning
confidence: 99%
See 1 more Smart Citation
“…Clinical reviews have reported that older persons are more susceptible to adverse effects of conventional antipsychotics, including parkinsonian side effects and tardive dyskinesia (80)(81)(82). Recent research on the use of novel antipsychotics among older adults is largely limited to open-label uncontrolled studies (85)(86)(87)(88) and a small number of controlled trials (89,90). Overall, the reports and reviews suggest that atypical antipsychotics should be considered as firstline agents in the treatment of schizophrenia among older persons.…”
Section: Schizophreniamentioning
confidence: 99%
“…There is good evidence that atypical antipsychotics are at least as effective as classical antipsychotics but are associated with significantly fewer serious side-effects (Beasely, 1996;Bondolfi et al, 1996;Tollefson et al, 1997;Taylor, 1997;Thomas and Lewis, 1998;King, 1998;Fleischhacker, 1999;Hawkins et al, 1999;Brown et al, 1999;Verma et al, 2001). Although atypical antipsychotics in general have fewer side-effects, particularly EPSEs, they may be associated with a number of important side-effects, e.g.…”
Section: Atypical Antipsychoticsmentioning
confidence: 99%